Roman homosexuality : ideologies of masculinity in classical antiquity - Williams, Craig A. (Craig Arthur), 1965- (Ideologies of desire., 1999)
Introduction 1. Roman Traditions: Slaves, Prostitutes, and Wives 2. Greece and Rome 3. The Concept of Stuprum 4. Effeminacy and Masculinity 5. Sexual Roles and Identities Conclusions.